Legal Politics And Constitutionality Of Changes In The Term Of Office Of Village Heads - Maulana, Thowil Fikri; Indrayati, Rosita; Ana, Ida Bagus Oka (Jurnal Justiciabelen, 2024)
The Village head is an important position at the local level. The village head's policies will greatly influence village life and village development. On January 23 2023, the Association of Indonesian Village Officials (APDESI) held a demonstration in front of the DPR building, one of the demands of which was to change the term of office for village heads to 9 years with the opportunity to serve for 2 terms. This research aims to determine the legal politics of changing the term of office of the head and the constitutionality of changing the term of office of the village head in the revision of the village law, and to determine the urgency of changing the term of office of the village head. The research method used in this research is normative research or library research using conceptual approach, statute approach and comparative approach. The legal politics of changing the term of office of the village head aims to improve the performance of the village head, which has often been hampered by social conflicts that occurred after the election of the village head, but this change is not in accordance with the principle of limiting power in countries that adhere to a democratic rule of law which has been implemented. outlined in the 1945 Constitution.